2001
DOI: 10.1203/00006450-200106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of PEPT1 and PEPT2 in Rat Small Intestine, Colon, and Kidney

Abstract: Mammalian peptide transporters (PEPT1 and PEPT2) play a pivotal role in the absorption of small peptides from the intestine and kidney, respectively, and in the disposition and targeting of peptide or mimetic drugs. However, there are few reports on the molecular basis of their regulation, especially in the young. The aim of this study was to determine the developmental expression of intestinal and renal oligopeptide transporters in rats from embryonic to adult ages. Intestinal segments were collected (i.e. du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 31 publications
(32 reference statements)
11
85
2
1
Order By: Relevance
“…In the fasted rats, both PepT1 mRNA abundance and protein expression increased three-fold. Due to the parallel changes in mRNA abundance and protein expression, this is suggestive of transcriptional regulation of PepT1, which is in agreement with the data of Shen et al (2001).…”
Section: Chapter II Literature Reviewsupporting
confidence: 91%
See 3 more Smart Citations
“…In the fasted rats, both PepT1 mRNA abundance and protein expression increased three-fold. Due to the parallel changes in mRNA abundance and protein expression, this is suggestive of transcriptional regulation of PepT1, which is in agreement with the data of Shen et al (2001).…”
Section: Chapter II Literature Reviewsupporting
confidence: 91%
“…Uptake then remained constant for 6 d postnatal, declined steadily, and reached adult levels by 50 d. More recently, abundance of PepT1 mRNA was reported to be greatest at 4 d of age in the jejunum of rats, and then decreased until reaching adult levels by 28 d of age (Miyamoto et al, 1996). Shen et al (2001) reported PepT1 mRNA abundance was maximal in all segments of the small intestine 3 to 5 d after birth. In the present study, sampling times did not begin until 2 wk of age, but the mRNA transcript that hybridized to our probe was present in all tissues studied by that time.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Comparative analysis using Northern and Western blotting techniques has shown an increase in the expression of PEPT1 in the small intestine immediately after birth and expression in the colon, which disappeared in adult stage (59). In the kidney, the expression levels of PEPT1 and PEPT2 increased steadily over time to reach maximal levels 2 wk after birth.…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%